Increased working hours per day and its impact on health of the workers: A review (GAIMS Journal of Medical Sciences, 2023)
Working conditions in most of the developing nations are not as per the guidelines. Government is changing the guidelines as per the benefit of the employers and side-lining the employees regarding many issues. With many occupations requiring heavy work and taking a lot of physical strength from manual labourers, the working time per day also affects the health of such workers. We investigated the different health impacts of increasing the working hours on labourers, and did a literature review on the same. We recommend that the workers in every occupational sector should work not more than 8-9 hours per day. They should get at least 30 minutes lunch break and one or two 15 minutes tea brakes during their shift to avoid exhaustion and fatigue from prolonged working.